"Unknown unknowns" and the tax knowledge gap: Power and the materiality of discretionary tax disclosures. (December 2021) - Edgley, Carla; Holland, Kevin
Highlights: Communication channels between institutional investors and senior executives. Disciplinary power combined with regulatory fear. Normalises routines that produce simplified plausible discretionary tax disclosures. Dramaturgical rituals allow some complex tax issues to be glossed over. Creates a tax knowledge gap; material unknown unknowns may exist. Abstract: Material misstatements in corporate tax disclosures have widespread economic and social impacts. Our study investigates how disciplinary power flows through communication channels between institutional investors and senior executives to normalise understandings of tax disclosures as an instrument of social control. Adopting a governmentality approach, we analyse interview data, in the UK and Australia, to query how power guides the willing subjectivity of senior executives to provide an account of tax performance that is aligned to institutional investor information expectations, given tax complexity. At this interface between financial reporting and tax regulation, disciplinary power, when combined with regulatory fear, routinize the production of simplified, plausible but sanitised stories. This provides institutional investors with what they need to know while avoiding the risk of attracting the attention of the tax regulator but limits the value of the information flow. Furthermore, mutually consensual, self-disciplining dramaturgical rituals between executives and institutional investors allow complex tax issues to be glossed over to focus on other more comfortable, productive areas of corporate performance. Power works in a subtle way to reproduce beliefs that complex tax details are less material and should be kept below the radar. This creates a tax knowledge gap with the potential for material 'unknown unknowns' to exist.